2015
DOI: 10.3109/17453674.2015.1040982
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic midshaft clavicular shortening does not result in relevant functional outcome changes

Abstract: Background and purposeShoulder function may be changed after healing of a nonoperatively treated clavicular fracture, especially in cases of clavicular shortening or mal-union. We investigated scapular orientations and functional outcome in healed clavicular fractures with and without clavicular shortening.Patients and methods32 participants with a healed nonoperatively treated midshaft clavicular fracture were investigated. Motions of the thorax, arm, and shoulder were recorded by standardized electromagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 33 publications
(55 reference statements)
0
28
1
3
Order By: Relevance
“…Five studies were retrospective [5, 2326] and one was prospective [27]. In four studies, determining the relationship between shortening and shoulder function was the primary study aim [23, 24, 26, 27]. Follow-up was at least 12 months in all studies, with a frequency-weighed mean of 4.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies were retrospective [5, 2326] and one was prospective [27]. In four studies, determining the relationship between shortening and shoulder function was the primary study aim [23, 24, 26, 27]. Follow-up was at least 12 months in all studies, with a frequency-weighed mean of 4.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…Stegeman and Postacchini additionally calculated the proportional shortening by dividing the overlap of fracture fragments by the sum of the length of the injured clavicle and the measured overlap [23, 25]. Shortening was also measured at different time points: on the index trauma radiographs [2427], or on radiographs taken after the fracture had united [5, 23]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these studies comprised highly specifi c patient cohorts composed exclusively of patients who had undergone corrective osteotomy. Several studies have found inferior clinical outcomes in the presence of shortening of 1.5-2 cm after healing [10][11][12]24], whereas others have not demonstrated such a relationship [14,25,26].…”
Section: Discussionmentioning
confidence: 99%